Cover Picture: Radical Chemistry and Reaction Mechanisms of Propane Oxidative Dehydrogenation over Hexagonal Boron Nitride Catalysts (Angew. Chem. Int. Ed. 21/2020). Issue 21 (23rd April 2020) - Zhang, Xuanyu; You, Rui; Wei, Zeyue; Jiang, Xiao; Yang, Jiuzhong; Pan, Yang; Wu, Peiwen; Jia, Qingdong; Bao, Zhenghong; Bai, Lei; Jin, Mingzhou; Sumpter, Bobby; et al.
Abstract : Hexagonal boron nitride is an emerging catalyst for the oxidative dehydrogenation (ODH) of alkanes to produce olefins with high selectivity and activity. In their Communication on page 8042, V. Fung, W. Huang, Z. Wu et al. report the first direct experimental evidence for gas‐phase methyl radicals (CH3 . ) in propane ODH over boron‐based catalysts. The presence of gas‐phase radicals is shown to be partially responsible for the generation of cracking products (C2 and C1 ) in propane ODH.